Réponses

Meilleure réponse !
2013-12-12T18:02:12+01:00
Bonsoir,

 (x - 1)(-x + 1) - (x - 1)(-2x + 1) = (x - 1)[(-x + 1) - (-2x + 1)] 
                                             = (x - 1) (-x + 1 + 2x - 1)
                                             = (x - 1) * x
                                             = x(x - 1) 
2013-12-12T18:05:09+01:00
Bonsoir

(x-1)(-x+1)-(x-1)(-2x+1)
Tu remarques que x-1 est le facteur qui revient 2 fois donc c'est celui que tu mets en facteur.

(x-1) ( -x+1)- (-2x+1)
(x-1) ( -x+1+2x-1)
(x-1)(x)